2018
DOI: 10.1172/jci.insight.98380
|View full text |Cite
|
Sign up to set email alerts
|

pDCs in lung and skin fibrosis in a bleomycin-induced model and patients with systemic sclerosis

Abstract: Fibrosis is the end result of most inflammatory conditions, but its pathogenesis remains unclear. We demonstrate that, in animals and humans with systemic fibrosis, plasmacytoid DCs (pDCs) are unaffected or are reduced systemically (spleen/peripheral blood), but they increase in the affected organs (lungs/skin/bronchoalveolar lavage). A pivotal role of pDCs was shown by depleting them in vivo, which ameliorated skin and/or lung fibrosis, reduced immune cell infiltration in the affected organs but not in spleen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 48 publications
4
35
0
Order By: Relevance
“…Two key studies have recently demonstrated the pathogenic role of pDCs in SSc pathogenesis 33 34. In line with these findings, we observed pDC infiltration to the skin when exposed to bleomycin, mimicking pDC accumulation in the skin of patients with SSc.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Two key studies have recently demonstrated the pathogenic role of pDCs in SSc pathogenesis 33 34. In line with these findings, we observed pDC infiltration to the skin when exposed to bleomycin, mimicking pDC accumulation in the skin of patients with SSc.…”
Section: Discussionsupporting
confidence: 89%
“…The role of pDCs in bleomycin model has been demonstrated recently 33 34. In line with this finding, the number of Siglec-H+ dermal pDCs was significantly increased in the skin after bleomycin treatment (figure 5A,B).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Elevated IFN gene signature in affected organs and in the blood is a key indicator of SSc disease severity, and has been shown to precede the onset of clinical fibrosis [13]. Since pDC are known to be the key cell type for activating IFN response to virus [3,4], along with increasing evidence suggesting mouse pDC are important for disease development [10,37], we developed our study to research the role of human pDC in inflammation and fibrosis of the skin. Specifically, we set out to determine whether targeting BDCA2 could suppress the IFN response and pro-fibrotic activation of pDC and ultimately inform the rationale for pDC targeted therapy for SSc.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of genes involved in chemotaxis, dendritic cell differentiation, inflammation and fibrosis in the lungs of pDC-depleted mice was also significantly reduced. Alongside this, B and T cells were also found to be reduced in the lungs, suggesting an important role for ongoing immune abnormalities induced by DCs [119]. In another bleomycininduced pulmonary fibrosis mouse model, DC accumulation in the lung was reduced through blocking of TGF-β with the use of inhibitor SB431542 [120].…”
Section: Dendritic Cellsmentioning
confidence: 99%